FDZ data description: Real-estate data for Germany (RWI-GEO-RED). Advertisements on the internet platform ImmobilienScout24 - Barbara Boelmann; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
The FDZ Ruhr provides a dataset on real estate advertisements in Germany for the years 2007 to 2017. The data is based on the internet platform ImmobilienScout24 and covers apartments and houses for sale and for rent. The data is available for scientific research only. The provided dataset covers detailed regional information and housing characteristics. This data report gives a brief overview on the data as well as its limitations and specifics. The data report is addressed to (potential) users of the data as support for data preparation.
Keywords: 330